Design of aluminum trihydroxide and P‐N core‐shell structures and their synergistic effects on halogen‐free flame‐retardant polyethylene composites. (15th April 2020) - Long, Shijun; Qiu, Di; Long, Ren; Li, Xun; Chen, Hanyu; Huang, Yiwan; Li, Xuefeng
Abstract: In order to improve the performance of inorganic/organic composites, aluminum trihydroxide (ATH) core composites with a styrene‐ethylene‐butadiene‐styrene block copolymer grafted with maleic anhydride (MAH‐ g ‐SEBS) shell phase, and P‐N flame retardant as a synergistic agent, were prepared through an interface design. The effects of polyethylene glycol (PEG) content on the interfacial interaction, flame retardancy, thermal properties, and mechanical properties of high‐density polyethylene (HDPE)/ATH composites were investigated by small angle X‐ray diffraction, rotational rheometer, limiting oxygen index, thermogravimetric analysis (TGA), and tensile testing. The ATH synergistic effects of P‐N flame‐retardant improved the combustion performance of HDPE/ATH/PEG(3%)/MAH‐ g ‐SEBS/P‐N (abbreviated as HDPE/MH3/M‐ g ‐S/P‐N) composite by forming more carbon layer, increased the elongation at break from 21% to 558% compared to HDPE/ATH, and increased the interface thickness from 0.447 to 0.891 nm. SEM results support the compatibility of ATH with HDPE increased and the interfacial effect was enhanced. TGA showed the maximum decomposition temperature of the two stages and the yield of the residue at high temperature increased first and then decreased with the increase of PEG content. Rheological behavior showed the storage modulus, complex viscosity, and the relaxation time initially increased and then decreased with the increase of PEG content indicating PEG, M‐ g ‐S, and ATH powder gradually formed a partial coating, then a full coating, and finally an over‐coated core‐shell structured model.